Principles and techniques of biochemistry and molecular biology - Wilson, Keith, 1936-; Walker, John M., 1948- (Cambridge, UK : Cambridge University Press, 2009)
'This best-selling undergraduate textbook provides an introduction to key experimental techniques from across the biosciences. It uniquely integrates the theories and practices that drive the fields of biology and medicine, comprehensively covering both the methods students will encounter in lab classes and those that underpin recent advances and discoveries. Its problem-solving approach continues with worked examples that set a challenge and then show students how the challenge is met. New to this edition are case studies, for example, that illustrate the relevance of the principles and techniques to the diagnosis and treatment of individual patients. Coverage is expanded to include a section on stem cells, chapters on immunochemical techniques and spectroscopy techniques, and additional chapters on drug discovery and development, and clinical biochemistry. Experimental design and the statistical analysis of data are emphasised throughout to ensure students are equipped to successfully plan their own experiments and examine the results obtained'--Provided by publisher
'This textbook integrates the theoretical principles and experimental techniques common to all undergraduate courses in the bio- and medical sciences'--Provided by publisher
Includes bibliographical references and index
Keywords: Biochemistry -- Textbooks; Molecular biology -- Textbooks